Early changes in glioblastoma metabolism measured by MR spectroscopic imaging during combination of anti-angiogenic cediranib and chemoradiation therapy are associated with survival - Ovidiu C. Andronesi (Nature Portfolio, 2017)
Metabolic imaging reveals anti-angiogenic (AA) therapy mechanisms in glioblastoma (GBM) GBM is the most common and aggressive type of malignant primary brain tumors (glioma). Patients with GBM have less than 5% survival at 5 years with the best existing treatment and progress is desperately needed to improve patient outcome. Imaging can guide development and clinical translation of new treatments, and can help to understand mechanisms of response and to optimize drug regimens in patients. AA therapy that targets the blood supply of tumors can benefit GBM patients as adjuvant therapy to standard chemoradiation, but the timing of combination therapy may be important to obtain the maximum benefit and minimize negative side effects. Tracking metabolic changes with magnetic resonance spectroscopic imaging (MRSI) during a phase II clinical trial of AA drug cediranib combined with chemoradiation shows that there is a therapeutic window within the first month where there is maximal synergy between the effects of the anti-angiogenesis and chemoradiation. Our data suggest that adjusting the dose of AA therapy during chemoradiation may be beneficial, and MRSI can be used as a precision medicine tool to identify the patients and time for adjusting the combination treatment.